Аппроксимация основных параметров распределения внешнего магнитного поля - Корбан, Николай Петрович (НТУ "ХПИ", 2010)
Рассматривается внешнее магнитное поле намагниченного ферромагнитного тела, содержащего дефект типа трещины. Разработан метод аппроксимации основных параметров распределения внешнего магнитного поля ферромагнитного тела с дефектом непосредственно от геометрических параметров дефекта. Проведены численные эксперименты. Произведена проверка адекватности аппроксимирующей модели и оценена погрешность аппроксимации.

External magnetic field of a magnetized ferromagnetic body containing a crack-type defect is examined. A technique for approximation of the basic parameters of the body external magnetic field distribution directly from geometrical parameters of the defect is developed. Numeral experiments are conducted. Verification of adequacy of the approximating model is made and error of the approximation is estimated.
Approximation of the basic parameters of external magnetic field distribution for a magnetized ferromagnetic body with a defect
Keywords: дефекты металлических изделий; намагниченные ферромагнитные изделия; геометрические параметры дефекта; основные параметры внешнего магнитного поля; magnetic field approximation; ferromagnetic body; crack-type defect; approximating model; numeral experiment